Ultra-high resolution snapshots of three multi-decadal periods in an Antarctic ice core - Skylar A Haines; Paul A Mayewski; Andrei V Kurbatov; Kirk A Maasch; Sharon B Sneed; Nicole E Spaulding; Daniel A Dixon; Pascal Bohleber (Journal of Glaciology, 2016)
We offer the first sub-seasonal view of glacial age archives from the Siple Dome-A (SDMA) ice core using the ultra-high resolution capabilities of a newly developed laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS; 121 μm sampling resolution) system capable of conducting multi-element glaciochemical analysis. Our ultra-high resolution data demonstrates that: (1) the SDMA ice core record can be annually dated based on seasonality in chemical inputs at a depth not previously possible using previous glaciochemical sampling methods, (2) winter accumulation at the SD site was greater than summer accumulation during the three late glacial periods selected (∼15.3, 17.3, 21.4 Ka ago) in this study and (3) resulting annual layer thicknesses results show greater variability than the current SD ice core depth/age model (Brook and others, 2005), possibly due to depositional effects such as wind scouring and/or decadal variability in snow accumulation that is not captured by the resolution of the current depth/age model.